Een boek als carrièrevehikel. De zeemansgidsen van Blaeu - van Netten, Djoeke (De Zeventiende Eeuw: Cultuur in de Nederlanden in interdisciplinair perspectief, 2012)
During the seventeenth century many editions of the pilot guide Het licht der zee-vaert and its successor the Zeespiegel were published by Willem Jansz Blaeu and later by his son Joan Blaeu. This paper extensively analyses and compares these different editions. The analysis shows that the main perspective on Blaeu as cartographer is too limited, as his pilot guides appear to be much more than just books with maps. Blaeu’s pilot guides are representational objects designed to launch his career. The as yet underexposed paratext does not only show the intended public of Willem and Joan Blaeu; it also demonstrates their network, political sympathies, and (lack of) pretentions.